Inclusive dialogues and reflections around scaling socio-technical innovations bundles: 3D animation - Nchanji, Eileen; Waswa, Boaz; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla (2024)
Increasing the adoption of technical and technological innovation in agriculture is crucial for a sustainable future. But how can we ensure that these innovations are effective and inclusive? The answer lies in co-designing and co-developing with farmers, taking into account their local context and everyday realities.